Performance Evaluation of Bearings - Sehgal, Rakesh (IntechOpen, 2012)
Bearings (both plain and rolling element) are used as important supporting elements for locating rotating components and confining their motion in desired direction. In order to ensure their operational reliability and desired life, these need to be properly designed/selected for an application more so because of ever increasing operational speeds. This requires the careful performance evaluation of different types of bearings considering aspects such as thermal stability, lubrication, contaminants in lubricants and controlling mechanism etc. The title of this book was specifically chosen as Performance Evaluation of Bearings. The present book is a compilation of different aspects contributing towards the performance evaluation of plain bearings (both journal and thrust), rolling element bearings and magnetic bearings.